The Phenomenon of Distribution and Impact of Zakat: How is it Practiced in Muslim Societies - Maulana, Gempa; Sulfinadia, Hamda; Efrinaldi, Efrinaldi; Ringgit, Awang (Samara: Journal of Islamic Law and Family Studies, 2023)
Zakat, as an act of worship and a form of obligation for Muslims, has a crucial role in creating social justice and reducing economic inequality in Muslim communities. This research aims to provide a deeper understanding of how the zakat distribution process takes place. This type of research is empirical juridical research, namely by studying directly in the field to see directly how zakat is distributed, and the implications for the beneficiaries. The research results show that First The majority of people tend to view zakat only as an obligation that must be fulfilled by individuals, without understanding the potential positive impact it can have on the economic recovery of their fellow citizens; second, The practice of distributing zakat is carried out through an event called